Changes of snatch technics in last 25 years period - Kruszewski, M.; Merda, W.; Kulej, M. (International Conference on Weightlifting and Strength Training. Conference Book, 1998)
Die Untersuchungen der Wettkampftechnik im Reißen der besten (europäischen) Gewichtheber ergaben: